Patient Satisfaction as a Quality Indicator in Pediatric Surgical Care: A Systematic Review. (23rd August 2013) - Espinel, Alexandra G.; Shah, Rahul; McCormick, Michael E.; Boss, Emily F.
Abstract : Objectives: Synthesize evidence‐based findings related to patient satisfaction as a quality indicator in pediatric surgical care. Methods: We conducted a qualitative systematic review, querying 4 standard search engines (1992‐2013) for studies specific to pediatric surgical fields in which patient/parent satisfaction or experience‐of‐care was a primary outcome measure. Data were systematically analyzed to determine study characteristics, setting, parent/patient focus, measure of experience, and bias. Two independent investigators independently reviewed all articles. Results: The initial search yielded 4678 publications (1433 duplicates) of which 170 underwent full text review. Thirty‐five were included for analysis; the majority (24/35, 77%) were published in the last 5 years. Studies examined experience of the child (4/35), parent (19/35), or both (12/35). Experience and satisfaction were evaluated either by validated self‐assessment instruments (9) or satisfaction tools (13), or by non‐standard institutional or author‐developed tools (20). Experience was measured in the outpatient (7), pre‐operative (11), peri‐operative (14), and post‐operative care (3) settings. Specific findings were unique to setting; however, pooled conclusions revealed that continuous communication with parents and an empathetic care team are associated with increased satisfaction with care. Conclusions: Experience‐of‐care is a valuable quality measure which is being more frequently evaluated as a mechanism to improve pediatric surgical care processes. Future investigation of patient experience in this discipline should employ validated tools for measurement. This review emphasizes that communication with families in each stage of the surgical process improves the patient experience and parent satisfaction. These findings bear significance as patient experience measures become routinely integrated with quality and reimbursement.